The Study on the Benefits and Constraints of Using Design and Build Procurement Method in the Construction Industry - Ching, Khai Linn (2015)
Design and Build (D&13) procurement is one of the procurement method being adopted in the construction industry in Malaysia. It is operated in such a way that the Contractor is the single sole who are responsible for both the design and construction works. Besides, it is one of the procurement which is able to provide with a more accurate estimation of cost and time mainly due to the Contractors who are employed for the execution of the works are those who have the experiences in the similar project, thus, able to supply the Clients with the overall estimate of cost and time needed to complete the whole works. For this research, study is conducted lo investigate the benefits and constraints arise to the construction parties included Clients and Contractors by using D&B procurement in the project construction. Besides, this research also served to identify the factors to be taken into consideration properly before selecting the most suitable procurement method to be applied for a project. Questionnaire is one of the method used in collecting the data to answer the objectives set up. Basically, the targeted population for the questionnaires arc specified to only those Clients and Contractors who have the experiences in participated in project using D&B procurement. From the data obtained, it showed that the common benefits provided by D&B procurement included the faster pace of construction, single point of responsibility and price certainty before the construction. From the analysis done, the initial price higher, inflexibility and substantial tendering cost are common constraints arise using D&B through the experiences from the Clients and Contractors. Regarding the key elements to be considered before choosing on the types of procurement method to be implemented, cost is considered to be most vital factors as compared to risk, time, complexity of construction etc.